Impact of Covid-19 on the education of children with disabilities in Malawi: reshaping parental engagement for the future - Singal, Nidhi; Mbukwa-Ngwira, Jenipher; Taneja-Johansson, Shruti; Lynch, Paul; Chatha, Gertrude; Umar, Eric (International Journal of Inclusive Education, 2021)
Covid-19 has led to unparalleled school closures and bought about extraordinary and unique challenges to ensuring continuity of learning for children across countries. This paper focuses on the educational experiences of children with disabilities in Malawi. Using a telephone survey, 99 parents/carers were interviewed about the impact of school closure on them and their child with disabilities. Parents reported as being overwhelmingly dissatisfied with the educational experiences of their child with disabilities, with a significant number reporting that they had no contact with the school or the teachers during closures. Children with disabilities were reported as spending very little time on formal learning activities. Nonetheless, parents were confident that their child with disabilities would return to school once these re-opened, as parents noted the loss of structure for their child’s day and increased loneliness arising from lack of contact with their friends. As schools reopen, the mental health of children with disabilities, alongside their learning, will need to be a priority. Finally, parents highlighted the need for more active involvement in their child’s schooling, so that they are able to support them better when they are at home.
Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2021.1965804 KerkoCite.ItemAlsoKnownAs: 10.1080/13603116.2021.1965804 2339240:QH5LTGZL 2405685:GDE8Q2X8
Keywords: Covid-19; Malawi; disability; education; parent; telephone survey

Malawi Economic Monitor : Investing in Digital Transformation - Hettinger, Patrick Shawn; Mboob, Ida S; Robinson, DanielleSimone; Nyirenda, Yalenga Loraine; Galal, Rami Mikko Ahmed; Chilima, Efrem Zephnath (World Bank, 2021)
Malawi Economic Monitor : Investing in Digital Transformation (English)
KerkoCite.ItemAlsoKnownAs: 2339240:4E283TFK 2405685:A54C4DV2

Language data for Malawi - Translators without Borders (Translators without Borders, 2021)
Open-source language data and maps about languages spoken in Malawi can improve how we communicate with communities in crisis.
KerkoCite.ItemAlsoKnownAs: 2339240:PCZ7W4YF 2405685:59QEPFPY

Language data for Malawi - Translators Without Borders (Translators without Borders, 2021)
Open-source language data and maps about languages spoken in Malawi can improve how we communicate with communities in crisis.
KerkoCite.ItemAlsoKnownAs: 2405685:85LDSX3J 4042040:U37DNB2H

Malawi Overview - World Bank (World Bank, 2021)
The World Bank Group supports Malawi’s efforts to reduce poverty and promote economic growth by working with the government, development partners, and civil society.
KerkoCite.ItemAlsoKnownAs: 2339240:JPCM7M8E 2405685:ZFIJNHAT

Scaling Personalised Learning Technology in Malawi - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:KWP37J8V 2339240:QWF5YPUM 2405685:3JNLR2A9 2405685:PMDAD9XJ

Scaling Personalised Learning Technology in Malawi: Lessons from our sandbox with onebillion - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:YWIIWQ2X 2405685:ZBHGFZXD

Leveraging Malawi’s Existing Digital Infrastructure to Boost Economic Growth - World Bank (World Bank, 2021)
The latest economic analysis of Malawi says the country has an opportunity to kickstart digital transformation by enabling the growth of a robust digital economy ecosystem
KerkoCite.ItemAlsoKnownAs: 2339240:F9MIWM7B 2405685:6ZM5SVJE

Malawi World Bank Approves $100 Million to Improve Skills Development Programs - World Bank (World Bank, 2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:P7XWBIFX 2405685:28VJ9MRA

Malawi World Bank Approves $100 Million to Improve Skills Development Programs Press Release - World Bank (2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:TL85HTPK 2405685:U7C5Y7FU 2405685:YAAV4TE4
Keywords: auto_merged

Malawi World Bank Approves $100 Million to Improve Skills Development Programs Press Release - World Bank (2021)
The World Bank today approved $100 million in financing from the International Development Association (IDA)* for Malawi to support increased access, particularly for female students, to skills development programs in priority areas of the economy that are most relevant to the labor market— now and in the future.
KerkoCite.ItemAlsoKnownAs: 2339240:TL85HTPK 2405685:U7C5Y7FU 2405685:YAAV4TE4
Keywords: auto_merged

Regional Communications Infrastructure Program (RCIP) Malawi - Global Infrastructure Hub (2021)
Only one in ten people in Malawi have access to information and communications technology (as of 2016). This is due to the high cost and complexity of developing the infrastructure and end-user service offering. However, the government plans to improve access to, and the affordability of, broadband connections. It is initiating projects to reach out to the most disadvantaged groups in society.
KerkoCite.ItemAlsoKnownAs: 2339240:N5IPDHHZ 2405685:U3PJDBD6

What we learnt in the Sandbox between onebillion, VSO Malawi and EdTech Hub (Sprint Review Draft) - Dinham, Nat; Plaut, Daniel; Rahman, Asad; Schmit, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4959811 2405685:M78SQRBW
Keywords: _EdTechHub_Output; _MELA_seen; _comingsoon; _r:AddedByZotZen

Malawi: Education Statistics - UNESCO Institute for Statistics (2021)
...
Last Modified: 2017-04-12 KerkoCite.ItemAlsoKnownAs: 2339240:ZU5965YA 2405685:2IXF4RSK

DigiMap – Digital Malawi Project - Public Private Partnership Commission (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BBWYTFNJ 2405685:N6IH9MK6

Case Study: TEAM Girl Malawi - Link Education International (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VTNN7IW4 2405685:C9CRSJF9

Case study: Team Girl Malawi - Link Education International (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:B9EEH33I

Language of Instruction Country Profile: Malawi - USAID (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:BK7VYG8H 2405685:UQ6JNHZN
Keywords: ⛔ No DOI found

Language of Instruction Country Profile: Malawi - USAID (United States Agency for International Development, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:QB34QBQL 4042040:R9YNHPBC

GDP per capita (current US$) - Malawi | Data - World Bank (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KXZG4ANK 2405685:VUM5AGV3

Coronavirus: Rwanda and Malawi shut schools as cases surge - AfricaNews (Africanews, 2021)
Africa has reported over 3.1 million cases and more than 76,000 deaths since the outbreak started,
KerkoCite.ItemAlsoKnownAs: 2339240:8HEGJ8DW 2405685:FTC6JMP2

Digital Skills Ecosystem and Gap Assessment in Malawi: Final Report - Ernst & Young (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WKQWSM76 2405685:YYDHA82Z

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

Digitalization in teaching and education in Malawi: Digitalization, the future of work and the teaching profession project - Saka, Tionge Weddington (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:9BDZPJAA 2405685:Z9HNTSCR

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:6HPRIAVP 2339240:7C7I9C4I 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:4MGG3JS3 2405685:5U948655 2405685:6UZHTZ8G 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH